Safety and efficacy of topically applied 0.5% and 1% pirfenidone in a canine model of subconjunctival fibrosis. (30th January 2019) - Westermeyer, Hans D.; Salmon, Beth; Baynes, Ronald; Yeatts, James; Khattab, Ahlam; Oh, Annie; Mowat, Freya
Abstract: Objective: To evaluate tissue levels, safety, and efficacy of topical ophthalmic 0.5% and 1% pirfenidone in decreasing subconjunctival fibrosis. Animal studied: Twelve normal beagle dogs Procedures: A 5 × 1 mm diameter silicone disk was implanted subconjunctivally in one eye, and then dogs were treated with topical 0.5% pirfenidone (n = 9) in artificial tears or artificial tears alone (n = 3) for 28 days. To evaluate tissue drug levels, a single sample of tears, conjunctiva, and aqueous humor was collected 30 (n = 3), 90 (n = 3), and 180 min (n = 3) following administration of the last drop of pirfenidone, respectively. Fibrous capsule thickness and staining for Ki67 and fibroblast activation protein alpha (FAPα) were evaluated histologically. After a 2‐week washout, the experiment was repeated in the opposite eye and using 1% pirfenidone. Results: Treatment with pirfenidone resulted in thinner fibrous capsules and decreased staining for FAPα with no adverse effects. The implant in one dog treated with pirfenidone extruded. There was no difference in tissue levels, capsular thickness, or staining for Ki67 or FAPα between dogs treated with 0.5% or 1% pirfenidone. Conclusions: Pirfenidone may decrease fibrosis following glaucoma shunt surgery and can potentially be used indefinitely due to minimal side effects.